Kombinasi Metode Georadar dan Geolistrik Resistivitas untuk Mendeteksi Keberadaan Batu Apung di Kota Mataram - Septhia Salwa Zulfatiha; Alfina Taurida Alaydrus; Syamsuddin Syamsuddin (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The eruption of Mount Samalas is the largest volcanic eruption event in Indonesia that occurred in 1257 AD. The eruption column reached 43 km, and produced pyroclastic material that was widely distributed on Lombok Island. Pyroclastic material from the eruption of Mount Samalas is characterized by the presence of pumice. Mataram City is one of the areas affected by the eruption of Mount Samalas. This study aims to determine the presence and distribution of pumice produced by the eruption of Mount Samalas in Mataram City, especially Ampenan District and Sekarbela District. The methods used in this research are georadar method and resistivity geoelectric method. The results obtained show that pumice is distributed in all research locations and found at varying depths, namely the range of 0 - 9 meters. The pumice found is mixed with other materials such as sand, gravel, silt, tuff, and clay.